Nie jestem „przedszkolanką” ani „panią z I–III”. Nauczyciele o postrzeganiu siebie i społecznym odbiorze ich pracy - Agnieszka Nowak-Łojewska (Problemy Wczesnej Edukacji)
The text refers to early education teachers and comprises reports on narrative research about teachers’ self-perception and social reception of their profession. It is based on a quality analysis of written statements issued by teachers and students preparing for teaching careers. The text contains the analysis of experiential material as well as theoretical reflections indicating both individual and social roles of teachers, their subjective and social status in the world, including their condition in society. The theses developed in this text and the quoted results from the study point at varied ways of thinking presented by teachers. The first trend indicates the pessimistic view of life of a modern teacher who finds it hard to accept the fact that they are not looked up to despite being conscious of gravity of their social role. The second, more optimistic trend is the one in which a teacher in addition to being aware of its social role perseveres in treating their profession as a vocation despite the lack of social respect and institutional support.